Pengaruh Disiplin Kerja Dan Komunikasi Terhadap Kinerja Karyawan Pada CV Kembar Jaya Parung - Winni Yanuarti Tika Puteri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to determine the effect of work discipline and communication on employee performance at CV Kembar Jaya Parung. The method used is quantitative method. This data collection technique is done by taking objects from samples called sampling or respondents, the sampling method using the saturated sample technique. The research sample is 75 respondents. The data analysis method used in the study includes instrument testing consisting of validity testing, reliability testing, classical assumption testing consisting of normality testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression testing, simple linear regression testing, correlation coefficients, determination coefficient tests, hypothesis testing consisting of partial t-tests and simultaneous f- tests. From the results of this study it can be concluded that work discipline has a positive and significant effect on employee performance with a label t-count value or (8.494> 1.993) and a significance value of 0.000 <0.05. Thus, H0 is rejected and H1 is accepted. Work discipline has a positive and significant influence on employee performance with a label t-value or (11.931> 1.993) and a significance value of 0.000 <0.05. Thus, H0 is rejected and H2 is accepted. Work discipline and communication have a positive and significant influence on employee performance with a value of Fcount> Ftable or (89.674> 3.12) and a significance value of 0.00 <0.05. Thus, H0 is rejected and H3 is accepted. Work discipline and communication on employee performance have a regression effect of Y = 4.601 + 0.328 (X1) + 0.551 (X2). The result of the correlation coefficient value of 0.845, it can be concluded that the variables of work discipline (X1) and communication (X2) together have a contribution to the influence of the employee performance variable (Y) of 71.4%, while the remaining 28.6% is influenced by other factors or variables not studied.